Pengaruh Media Interaktif Berbasis Wordwall Terhadap Hasil Belajar Peserta Didik Kelas IV Mata Pelajaran IPAS Sekolah Dasar Negeri 51 Sungai Raya - Safitri, Bela; Setyowati, Dessy; Farisi, Salman Al (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to determine the effect of Wordwall-based interactive learning media on student learning outcomes on culturally rich Indonesian material. This research uses quantitative methods. With a nonequivalent control group design research design. The population included in this study consists of 31 students from class IV A. Meanwhile, class IV B also has 31 students. The data collection technique in this research is in the form of tests, and the analysis is conducted through descriptive quantitative methods. The results of the research show that the use of Wordwall-Based Interactive Media Influences the Learning Outcomes of Class IV Students in Science Subjects at State Elementary School 51 Sungai Raya. This is shown by the results of the t test, namely t count > t table (4,586 > 1671) with a significance level of 5% or 0.05. The average posttest score for the experimental class was 79.58, better than the average posttest score for the control class, which was 64.90 at the specified kkm, namely 70.